THE PECULIARITIES OF TRANSLATING LEXICO-SEMANTIC STRUCTURES IN GIACOMO LEOPARDI’S POETRY - Karpan, Olha (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2025)
This article explores the complexities involved in translating the lexico-semantic structures found in Giacomo Leopardi’s poetry, one of the greatest figures in Italian and world literature. By focusing on rhythmic and intonational challenges, it reveals the pivotal role of preserving the poet’s philosophical depth in the target language. The study compares the distinct translation approaches of Mykhailo Orest and Hryhorii Kochur, who each attempted to capture Leopardi’s nuanced blend of existential contemplation and lyrical beauty. Special attention is given to the cultural and historical circumstances that shaped Leopardi’s trademark pessimism, demonstrating how those factors demand strategic adaptation and compromise on the part of translators. Consequently, the article highlights not only the diverse methods employed to maintain the poet’s unique tone and imagery but also the broader implications of these methods for the evolution of Ukrainian literary translation. The concluding section outlines possible directions for future research, emphasizing the significance of interdisciplinary approaches that integrate literary analysis, linguistic theory, and cultural studies. Ultimately, the author argues that any successful rendering of Leopardi’s poetic oeuvre must account for both the textual intricacies of his language and the profound emotional resonance embedded in his philosophical vision, making his works a perpetual challenge and a source of fascination for translators worldwide. _______________ References • Aleksienko, (1988). Svit poezii Dzhakomo Leopardi. U Dzhakomo Leopardi. Poezii (s. 5–32). Kyiv: Dnipro. • Ivleva, O. (2025). Svit Dzhakomo Leopardi v interpretatsii perekladachiv. Mariupolskyi molodizhnyi naukovyi forum: tradytsiini y novitni aspekty doslidzhennia i vykladannia inozemnykh mov i literatury. Data zvernennia 18 sichnia 2025. Retrieved from https://mu.edu.ua/storage/MSU/pages/conferences/2021/ • Bellucci, G. (1996). Leopardi e i contemporanei: testimonianze dall’Italia e dall’Europa in vita e in morte del poeta. Firenze: Ponte alle Grazie. • Blasucci, (1985). Leopardi e i segnali dell’infinito. Bologna: Mulino. • Il pensiero storico e politico di Giacomo Leopardi. (1989). Firenze: Olschki. • Jonard, (1977). Giacomo Leopardi: essai de biographie intellectuelle. Paris: Les Belles Lettres. • Leopardi, (1974). Canti. Edizione di riferimento. Milano: Rizzoli. • Solmi, (1975). Studi e nuovi studi leopardiani. Napoli: Riccardo Ricciardi. • Leopardi, G. (1974). Edizione di riferimento (p. 125). Milano: Rizzoli.